From Affectivity to Subjectivity - Lotz, C. author. aut Link
IX, 178 p.
Keywords: Shows that Husserl's Phenomenology and its key concept, subjectivity, is based on a concrete anthropological structure, such as self-affection and the bodily experience of the other.